2021
DOI: 10.25259/sni_730_2020
|View full text |Cite
|
Sign up to set email alerts
|

The utility of deep brain stimulation surgery for treating eating disorders: A systematic review

Abstract: Background: Deep brain stimulation (DBS) has demonstrated preliminary success as a treatment for neuropsychological disorders including obsessive-compulsive disorder and substance use disorder. This systematic review aims to assess the use of DBS in treating eating disorders (EDs) to determine its utility and the extent of adverse effects. Methods: A PubMed search following PRISMA guidelines was executed to find studies encompassing DBS as a treatment of ED. Outcomes were extracted from the literature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Notably, some studies have also revealed a positive impact of DBS on quality of life (Wu et al., 2013). In a recent systematic review of 11 studies that explored the effect of DBS in eating disorders (ED), it was found that 41.5% of the participants achieved normal BMI after follow‐up (Potes et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, some studies have also revealed a positive impact of DBS on quality of life (Wu et al., 2013). In a recent systematic review of 11 studies that explored the effect of DBS in eating disorders (ED), it was found that 41.5% of the participants achieved normal BMI after follow‐up (Potes et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Implantable sensors can also be used for neural sensing (e.g., brain neural recording), intracranial neurostimulation (invasive deep brain stimulation, DBS), neuromodulation, and neurofeedback [25][26][27][28][29][30][31][32][33][34][35][36]. The neuroanatomical areas of major interest for the treatment of AN have been the brain's subcallosal cingulate cortex and the nucleus accumbens [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have focused on eating behavior and weight gain as indicators of successful outcomes [ 43 ], and much less on body image issues [e.g., 40] . First, it is important to recognize that weight gain is just one of many other important markers of a successful treatment outcome [ 33 ]. Second, it is also worth noting the caveats of implementing intracranial sensors (e.g., undergoing neurosurgery, using durable and flexible biocompatible materials, cytotoxicity) [ 34 ], and most importantly the ethical concerns that can generate these interventions [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implantable sensors can also be used for neural sensing (e.g., brain neural recording), intracranial neurostimulation (invasive deep brain stimulation, DBS), neuromodulation, and neurofeedback [25][26][27][28][29][30][31][32][33][34][35][36]. The neuroanatomical areas of major interest for the treatment of AN have been the brain's subcallosal cingulate cortex and the nucleus accumbens [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%